Risks of HACCP Plan Implementation for Food Safety at Business Startup PT. BERAS JAGUNG NUSANTARA - Tri Nurfitriati; Tantri Yanuar Rahmat Syah; Semerdanta Pusaka; Dadan Ramdhani (Penerbit Kemala Indonesia, 2020)
This study aims to ensure that business activities will be carried out in accordance with what was planned and also be able to obtain a current position of the company by the direction of company's goals and target achievement. In this study, is also influenced by the strategy we choose to achieve the goal. A company must know the amount of demand for products made by looking at market conditions and company strategy. The company's operational activities are very likely to be carried out so that the company can offer more competitive prices compared to imported products that have previously entered the market. All companies must be faced a financial and operational risks, including PT. Beras Jagung Nusantara, therefore every company needs Enterprise risk management (ERM) or enterprise risk management to overcome and reduce any company risks that may arise.